The Defense Mechanism of the Colonel Kalawa’s Character in the Drama Script Our Beloved President by Agus Noor: Sigmund Freud's Psychoanalysis - Ahyudi, Ahyudi; Burhanuddin, Burhanuddin; Mahyudi, Johan (Lembaga Penelitian dan Pendidikan Mandala, 2024)
The problem in this study is how the defense mechanism of the character Colonel Kalawa in the drama script of Our Beloved President by Agus Noor based on Sigmund Freud's psychoanalysis study. The purpose of this study was to determine the defense mechanism of the character Colonel Kalawa in the drama script of Our Beloved President by Agus Noor based on Sigmund Freud's psychoanalysis study. The theory used in this study is Sigmund Freud's defense mechanism. This research is qualitative. The source of data in this study is Agus Noor's beloved drama script President Kita. The data collection methods used are library methods, and documentation. Based on the results of data analysis conducted on the drama script of our Beloved President, it can be concluded that the character of Colonel Kalawa in the drama script of our Beloved President has 6 defense mechanisms based on the psychoanalytical perspective of Sigmudn Freud. The results of data analysis in this study, it can be known various defense mechanisms of Colonel Kalawa's figure, namely there are 3 data regarding the concept of repression defense that arises in the form of symbolization. There are 2 data included in the defense of sublimation in the form of self-adjustment and attitude change. Then there are 7 data on the concept of projection defense in the form of blaming others. Furthermore, there is 1 data regarding the defense of the diversion in the form of finding vent. Furthermore, there are 8 rationalization self-defense data in the form of seeking justification. As well as the last there are 6 data that belong to the defense of aggression and apathy in the form of anger and anxiety.